2007
DOI: 10.1007/s10517-007-0306-5
|View full text |Cite
|
Sign up to set email alerts
|

On the accuracy of evaluations of temporal characteristics of visual perception

Abstract: We studied the accuracy of evaluations of the temporal characteristics of visual perception: critical frequency of light flickers, time of perception, and time of visual analyzer recovery. Results of comparison of the accuracy of evaluations are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Visual temporal resolution processes in humans can be evaluated by measuring the Critical Flicker Frequency threshold (CFFt)[1], [2], defined as the frequency at which a flickering light is perceived as a continuous light [3], [4]. In normal subjects, several studies have investigated the influence on CFFt of several factors including age, blood carbon dioxide, and site of retinal stimulation [5][10] and confirmed that CFFt is a reliable test for the investigation of visual temporal resolution [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual temporal resolution processes in humans can be evaluated by measuring the Critical Flicker Frequency threshold (CFFt)[1], [2], defined as the frequency at which a flickering light is perceived as a continuous light [3], [4]. In normal subjects, several studies have investigated the influence on CFFt of several factors including age, blood carbon dioxide, and site of retinal stimulation [5][10] and confirmed that CFFt is a reliable test for the investigation of visual temporal resolution [11].…”
Section: Introductionmentioning
confidence: 99%
“…Visual temporal resolution processes in humans can be evaluated by measuring the Critical Flicker Frequency threshold (CFFt) [1] , [2] , defined as the frequency at which a flickering light is perceived as a continuous light [3] , [4] . In normal subjects, several studies have investigated the influence on CFFt of several factors including age, blood carbon dioxide, and site of retinal stimulation [5] [10] and confirmed that CFFt is a reliable test for the investigation of visual temporal resolution [11] . Although the contribution of anterior visual pathways to the temporal analysis of visual stimuli is well established [12] [14] , the physiological basis of CFFt and in particular the role played by the cortical areas in conscious perception of a flickering light is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…• accepting and perceiving information (the initial stage of receiving information from different sensory sources) [22]; • evaluating and processing information (finding out the most important information and, then, its analysis and evaluation) [23]; • making a decision (planning a certain activity) [24]; • implementing the decision made (physical movement) [24]. One of the key elements of different models of operator's responses is reasoning or conclusion that make the ground for making a final decision [25,26].…”
Section: The Model Of a Virtual Environment For The Training Of Ergatmentioning
confidence: 99%
“…La frecuencia en que una luz intermitente se percibe como continua es conocida como Frecuencia Critica de Fusión (FCF) (Seitz, Nanez, Holloway, & Watanabe, 2005). La RTV es considerada como una medida de la velocidad de procesamiento del sistema nervioso y del nivel de activación cortical (Nardella, Rocchi, Conte, Bologna, Suppa, & Berardelli, 2014) y se ha confirmado que la determinación de la FCF es una prueba confiable para la investigación de la RTV (Petukhov, Rozhentsov, & Aliev, 2007).…”
Section: Introductionunclassified